CYP2D6 Substrate Dispensing Among Patients Dispensed Mirabegron: An Administrative Claims Analysis - Mary E. Ritchey; Jingjun Wang; Jessica C. Young; Rajat Chandra; Adam Carrera; Noelia Goti; John R. Horn; Cynthia J. Girman (Adis, Springer Healthcare, 2022)
Abstract Background Overactive bladder (OAB) is characterized by the presence of bothersome urinary symptoms. Pharmacologic treatment options for OAB include anticholinergics and β3-adrenergic agonists. Use of β3-adrenergic agonists may result in similar treatment efficacy with a decreased side effect profile compared with anticholinergics because high anticholinergic burden is associated with cardiovascular and neurologic side effects. However, the β3-adrenergic agonist mirabegron, one of two approved drugs within this class, is a moderate cytochrome P450 (CYP) 2D6 inhibitor, and coadministration of drugs that are CYP2D6 substrates with mirabegron may lead to adverse drug effects. Objective The aim of this study was to quantify how often CYP2D6 substrates were dispensed in patients receiving mirabegron among adults of any age and among those ≥ 65 years of age. Methods In this retrospective descriptive analysis, a deidentified administrative claims database in the United States, IQVIA PharMetrics® Plus, was used to identify dispensing claims for CYP2D6 substrates and mirabegron from November 2012 to September 2019. Prevalence of CYP2D6 substrate dispensing was assessed in patients dispensed mirabegron among all adults ≥ 18 years old and additionally among a cohort of those ≥ 65 years old. Patient baseline profiles at the time of mirabegron and CYP2D6 substrate codispensing and at the time of mirabegron dispensing were compared. CYP2D6 substrates were categorized as those with the potential for increased risk of QT prolongation, with anticholinergic properties, with narrow therapeutic index (NTI), contraindicated or having a black box warning when used with CYP2D6 inhibitors, or used for depression or other psychiatric disease. Dispensing data and patient profiles were summarized descriptively. Results Overall, 68.5% of adults ≥ 18 years old dispensed mirabegron had overlapping dispensings for one or more CYP2D6 substrate; 60.6% and 53.6% had overlapping dispensings for CYP2D6 substrates with anticholinergic properties or risk of QT prolongation, respectively. CYP2D6 substrates with NTI, contraindicated with CYP2D6 inhibitors, or for psychiatric use were codispensed in 17.7%, 16.6%, and 38.0% of adult mirabegron users, respectively. Mirabegron users receiving one or more concurrent CYP2D6 substrate were more likely to be older, have more comorbidities and baseline polypharmacy, and have increased healthcare resource utilization compared with those without concurrent CYP2D6 substrates. Commonly codispensed CYP2D6 substrates included hydrocodone, oxycodone, tramadol, metoprolol, and tamsulosin. Findings were similar for patients in the older cohort (≥ 65 years old), with 72.1% receiving overlapping CYP2D6 substrates. Conclusions Codispensing of CYP2D6 substrates, especially those with anticholinergic properties or risk of QT prolongation, was common among adults and older adults receiving mirabegron. Results highlight the need for improved awareness of CYP2D6 substrate prescribing among patients receiving pharmacologic treatment for OAB that inhibits the CYP2D6 pathway.